POSSIBILIDADES NO ENSINO DE MATEMÁTICA ATRAVÉS DE MATERIAIS DIDÁTICOS VIRTUAIS - Roncaglio, Viviane; Souza, Marco A. d.; Dorneles, Lecir D.; Piva, Cláudia; Uecker, Taciana (Salão do Conhecimento, 2013)
Resumo